Determinação de resíduos de agrotóxicos em fisalis (Physalis peruaviana L.) empregando QuEChERS modificado e UHPLC-MS/MS - Munoz, Natalia Cadavid (2016)
In this study a fast and effective multiresidue method for the determination of 42 pesticides in goldenberry was developed and validated. A modified QuEChERS method was established for sample preparation followed by ultra-high-performance liquid chromatographic–tandem mass spectrometry (UHPLC–MS/MS) determination with electrospray ionization in a triple quadrupole system. Validation results were satisfactory, since the proposed method presented recoveries between 70 and 114% with relative standard deviations (RSD) <20% for blank samples spiked from 5 to 25 μg kg-1. The method limits of detection and of quantification were 1.5 and 5 μg kg-1, respectively. Matrix effect ranged from -32 to 218% and was compensated using matrix matched calibration. Method linearity was established from 2.5 to 100 μg kg-1 with r2 ≥0.99. The proposed method combines the advantages of a simple and fast sample preparation step by a modified QuEChERS method with the high selectivity and sensitivity of the UHPLC-MS/MS system using selected reaction monitoring. Method was successfully applied to real samples, proving to be an efficient alternative for routine analysis. Residues of five pesticides were found in the samples evaluated.